The Effect of 2,4 Dimethylamine salt on the Blood, Liver and Muscle of Oryclotagus Cuniculus - Iniobong, R. Inyang; Dudutari, E. Patani; Sylvester, C. Izah (Journal of Plant and Animal Ecology, 2020)
Aminoforce containing 720g/l of 2,4-dimethylamine salt induced changes on some enzymes and electrolytes in the male Oryclotagus cuniculus (New Zealand rabbit) were assayed. The organisms were exposed to varying sub-lethal concentrations of the toxicant (720g/l). The concentrations were prepared by pipetting 0.4mls, 0.8mls and 0.12mls making it up to 1.5L clean water in a metal container to make 2.0 mgl-1, 4.0 mgl-1 and 6.0 mgl-1. Aspartate amino transferase (AST), Alanine amino transferase (ALT) and Acid phosphatase (ACP) were assayed in the liver and blood. Results showed that aspartate amino transferase values in the liver and blood were significant (p<0.05) across the concentration of the toxicants. Aspartate amino transferase increased as the concentration of the toxicant increased in the liver, and decreased as the toxicant concentration increased in the blood. Alanine amino transferase in the blood and liver were akin to AST while ACP values increased in the blood and decreased in the liver as the concentration of the toxicant increased. Electrolytes (Sodium (Na+), potassium (K+) and magnesium (Mg2+) ions) showed statistical deviation across the various concentration of the toxicants. Chloride ion values stabilized in the experimental group being not significantly different (p>0.05) across the various concentration of the toxicants. From the study, AST, ALT and ACP are suitable biomarkers for showing sub-lethal effect of aminoforce on Oryclotagus cuniculus. The effects recorded clearly unveiled the potential effect of this xenobiotics on Oryclotagus cuniculus. Therefore, exposure of Oryclotagus cuniculus to this toxicant will affect the organism’s physiological responses and over prolong period of time it could lead to death. Additionally, via food chain man may be affected. The use of this toxicant close to rabbittory should be done with utmost caution.
Keywords: Aspartate amino transferase; Alanine amino transferase; Acid phosphatase; Electrolytes; Oryclotagus cuniculus